PERANAN KOMITE AUDIT MENGOPTIMALKAN FUNGSI AUDITOR INTERNAL DALAM PENERAPAN GOOD CORPORATE GOVERNANCE DI PT BNI.tbk - Firmansyah, Arif (Syiar Hukum, 2010)
Bank is an intermediary between a party who have surplus of funds and those who have lack of fund. In this respect,Â  public trust depends on bank work performance and its ability to manage risk, professionalism and integrity of the bank board and public transparency.Â  This article discusses the role of Audit Committee to optimize the internal auditor function in the implementation of good corporate governance in BNI 1946 Limited Company.Â Â  The article examinesÂ Â  some challenges of the Audit Committee in optimizing such function.Â  These include the Audit Committeeâs inability to (1) boost the Bank CommissionerÂ  in doing supervision and (2) assist Supervision Internal Unit in obtaining accurate data. The author recommendsÂ  that accountability and commitment of company board should be conducted professionally in order to effectively optimize theÂ  role of Audit Committee.Â  Â